Kemampuan pemahaman matematis siswa smp pada materi perpangkatan dan bentuk akar secara daring pada masa pandemi covid-19 di desa jayaraga - Pranitha Agustina Hidayat; Reni Nuraeni (Institut Pendidikan Indonesia, 2022)
Mathematical understanding ability is the ability to classify mathematical objects and be able to interpret mathematical ideas or concepts. Online learning or electronic learning (e-learning) is an electronic-based learning process, towards the continuity of learning activities during the COVID-19 pandemic in accordance with policies issued by the government by using various media that support learning. This study aims to determine the ability of students' mathematical understanding in solving problems on the matter of Powers and Root Forms. The type of research used is qualitative research. This research was conducted in Jayaraga Village with research subjects of as many as three junior high school students in class IX. The data collection techniques in this research are using written tests and interviews. The results of this study indicate that students who have a high mathematical understanding ability are able to complete 3 indicators of mathematical understanding ability, while students who have a moderate mathematical understanding ability are only able to complete 2 indicators of mathematical understanding ability, and students who have the low mathematical understanding ability are not able to complete all indicators of understanding ability mathematical. Kemampuan pemahaman matematis adalah kemampuan mengklasifikasikan objek-objek matematika dan mampu menginterpretasikan gagasan atau konsep matematika. Pembelajaran daring atau pembelajaran elektronik (e-learning) merupakan sebuah proses pembelajaran berbasis elektronik, terhadap keberlangsungan kegiatan pembelajaran di masa pandemi COVID-19. Penelitian ini bertujuan untuk mengetahui kemampuan pemahaman matematis siswa dalam menyelesaikan soal-soal pada materi Perpangkatan dan Bentuk Akar. Jenis penelitian yang digunakan adalah penelitian kualitatif. Penelitian ini dilakukan di Desa Jayaraga dengan subjek penelitian sebanyak tiga orang siswa SMP kelas IX. Adapun teknik pengumpulan data dalam peneltian ini adalah menggunakan tes tulis dan wawancara. Hasil penelitian ini menunjukan bahwa siswa yang memiliki kemampuan pemahaman matematis tinggi mampu menyelesaikan 3 indikator kemampuan pemahaman matematis, sedangkan siswa yang memiliki kemampuan pemahaman matematis sedang hanya mampu menyelesaikan 2 indikator kemampuan pemahaman matematis dan siswa yang memiliki kemampuan pemahaman matematis rendah tidak mampu menyelesaikan semua indikator kemampuan pemahaman matematis.